Clinical Predictors of Testicular Torsion in Patients with Acute Scrotum; a Cross-Sectional Study - Sazgar, Mohammad; Montazer, Seyed Hossein; Hosseininejad, Seyed Mohammad; Jahanian, Fatemeh; Rezaimehr, Behkam; Behbohaninia, Mohammad; Aminiahidashti, Hamed (Archives of Academic Emergency Medicine, 2022)
Introduction: Testicular torsion is an important and critical issue in patients with acute scrotum referring to emergency department (ED). Early detection is very important to save the testicles. This study aimed to determine the diagnostic accuracy of clinical variables in predicting the presence of testicular torsion. Methods: This prospective cross-sectional study was done using the information of patients hospitalized from September 2015 to September 2020, with complaint of acute scrotum (ICD 10 code: N50.8), referring to ED for evaluation of the clinical predictors of testicular torsions, which were confirmed by surgery. Results: 81 patients with the mean age of 20.07 ± 9.64 (3- 45) years were studied. After surgical exploration, 70 patients (86.4%) had testicular torsion. Patients with torsion had lower age (p < 0.0001), lower time from symptom to ED visit (p < 0.0001), sudden onset pain (p = 0.003), left side pain (p < 0.0001), and lower white blood cell (WBC) count (p = 0.001). The frequency of dysuria (p = 0.032), diarrhea/vomiting (p = 0.005), and fever (p = 0.002) was significantly lower in patients with torsion. The cremasteric reflex was absent in 57 (81.4%) cases who suffered from testicular torsion (p = 0.001). Based on the results of binary logistic regression analysis, age (B = -0.175, SE = 0.45; p < 0.0001) was the sole independent predictor of testicular torsion. The highest area under the receiver operating characteristics (ROC) curve in predicting the presence of torsion belonged to lower age [91.0 (95%CI: 83.2 – 98.7)], pain in left testis [0.931 (95%CI: 0.828-0.987)], and lower WBC count [0.805 (95%CI: 0.684-0.926)], respectively. Conclusion: It seems that clinical variables are not accurate enough to be considered as the sole predictor of testicular torsion and they should be used with caution and in combination with other available screening tools like Doppler ultrasonography in this regard.